Impact of High Contact Stress on the Wear Behavior of U75VH Heat-Treated Rail Steels Applied for Turnouts - Ruimin Wang; Guanghui Chen; Nuoteng Xu; Linyu Sun; Junhui Wu; Guang Xu (Metals, 2025)
Considering the greater contact stress of turnout rails during wear and the development of heavy-haul railways, twin-disc sliding–rolling wear tests were performed on U75VH heat-treated rail steels applied for turnouts under high contact stress ranging from 1980 MPa to 2270 MPa. The microstructure of the worn surfaces was analyzed using optical microscope (OM), scanning electron microscope (SEM), 3D microscope, electron backscatter diffraction (EBSD), and hardness tests. The results indicated that after 10 h of wear, the weight loss was 63 mg at a contact stress of 1980 MPa, while it reached 95 mg at a contact stress of 2270 MPa. At a given contact stress, the wear rate increased with increasing wear time, while a nearly linear increase in wear rate was observed with increasing contact stress. As wear time and contact stress increased, the worn surface showed more pronounced wear morphology, leading to greater surface roughness. Crack length significantly increased with wear time, and higher contact stress facilitated crack propagation, resulting in longer, deeper cracks. After 10 h of wear under a contact stress of 2270 MPa, large-scale cracks with a maximum length of 128.29 μm and a maximum depth of 31.10 μm were formed, indicating severe fatigue wear. Additionally, the thickness of the plastic deformation layer increased with the wear time and contact stress. The surface hardness was dependent on the thickness of this layer. After 10 h of wear under the minimum and maximum contact stresses, hardening rates of 0.39 and 0.48 were achieved, respectively.